Preface - Herawan, Tutut (Journal of Information Systems Research and Practice, 2024)
The Volume 2 Issue 4 of JISRP will be available online on October 14th, 2024 for the regular issue of December 2024. The issue has been available online for accepted papers (uncorrected proofs).